Integrating enzymatic responses to organic chemical exposure with total oxyradical absorbing capacity and DNA damage in the European eel Anguilla anguilla - REGOLI, F.; WINSTON, G. W.; GORBI, S.; FRENZILLI, G.; NIGRO, M.; CORSI, I.; FOCARDI, S. (Environmental Toxicology and Chemistry, 2003)
In this work, susceptibility to oxidative stress was analyzed under laboratory conditions in the European eel Anguilla anguilla. Eels were treated with increasing concentrations of benchmark environmental pollutants, namely, benzo[a]pyrene ([BaP], at 0, 0.1, 1, 10, and 50 mg/kg), P-naphthoflavone ([BNF], at 0, 0.1, 1, 10, and 50 mg/kg), Arochlor(R) 1254 (at 0, 0.1, 1, 10, and 50 mg/kg), and 2,3,7,8-tetrachlorodibenzo p-dioxin ([TCDD]; at 0, 0.01, 0.1, 1, and 2 mug/kg). The integral relationships were analyzed between induction of ethoxyresorufin O-deethylase (EROD) activity, its involvement in perturbing oxyradical metabolism, and the role of cytochrome P450 and/or oxidative stress in mediating genotoxic effects. To reveal whether the oxidative status in exposed organisms was altered as a result of chemical exposure, measurements of the main endogenous antioxidant defenses were integrated with the measurement of total oxyradical scavenging capacity (TOSC) toward peroxyl radicals and hydroxyl radicals (-OH). This approach permits discriminating the resistance of a tissue toward different forms of oxyradicals, thereby indicating a differential role for specific reactive oxygen species (ROS) in perturbing the balance between prooxidant and antioxidant mechanisms. All the analyzed chemicals promoted EROD induction (reflective of CYP1A) and altered either the levels or the activities of the antioxidants studied, which might be anticipated to exert alterations in oxyradical metabolism. Analysis of TOSC suggested the prevalence of metabolic oxidative pathways leading to the more reactive -OH on exposure to the chemicals studied. Of these chemicals, enhanced EROD activity correlated with genotoxic damage only in the cases of the nonhalogenated hydrocarbons BaP and BNF. The highest degree of genotoxic damage was consistently observed in organisms in which the capacity to absorb or scavenge -OH was lowest. These data suggest a general relationship between oxidative stress and loss of DNA integrity in juvenile eels exposed ...